A modified neutral-point balancing space vector modulation technique for three-level neutral point clamped converters in high speed drives - Li, Chen; Yang, Tao; Kulsangcharoen, Ponggorn; Lo Calzo, Giovanni; Bozhko, Serhiy; Gerada, Chris; Wheeler, Patrick (Institute of Electrical and Electronics Engineers, 2018)
This paper describes a high performance neutral point voltage balancing technique for a Neutral point clamped (NPC) Converter. Conventional neutral point voltage balancing methods do not function well under low power factor, low pulse ratio and near-unity modulation index operation conditions. These conditions are essentially dominant operation conditions for aircraft starter/generator systems. This paper introduces an alternative space vector modulation technique for three-level NPC converters in an aircraft starter generator system. The selection of voltage space vectors is optimized for high modulation index and low power factor operation. Disturbances caused by low pulse ratio is also compensated. The proposed method maintains neutral point voltage balance and ripple minimization over the full range of operating conditions. The paper also provides a detailed analysis into the sources of neutral point voltage imbalances and ripples in high speed drives with deep flux weakening. Simulation results obtained from a Simulink/PLECS model and experimental results obtained from a 45kVA, 32krpm aircraft starter generator test rig proves the proposed method eliminates the neutral point voltage imbalance and significantly reduces the neutral point voltage ripple.